Application of Normalization Process Theory in Discharge Planning: A Systematic Review of Implementation Strategies and Outcomes - Rahayu U; Ibrahim K; Herman H (Journal of Multidisciplinary Healthcare, 2025)
Urip Rahayu,1,2 Kusman Ibrahim,2 Herry Herman3 1Doctoral Program, Faculty of Medicine, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Department of Medical-Surgical Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 3Department of Orthopaedic Surgery, Universitas Padjadjaran – Hasan Sadikin General Hospital, Bandung, IndonesiaCorrespondence: Urip Rahayu, Faculty of Nursing, Universitas Padjadjaran, Jl. Raya Ir. Soekarno KM. 21 Hegarmanah, Jatinangor, Sumedang, West Java, 45363, Indonesia, Tel +6281220201942, Fax +6202287793411, Email urip.rahayu@unpad.ac.idBackground: Discharge planning is an important aspect of healthcare to ensure continuity of patient care after hospital discharge. Normalization Process Theory (NPT) has been used to understand how discharge planning interventions can be implemented effectively in clinical practice.Purpose: This review aimed to explore the use of Normalization Process Theory (NPT) in patient discharge planning and how this theory is applied in various healthcare contexts.Methods: A systematic review was conducted using the PRISMA method, using four international databases: PubMed, Scopus, Taylor & Francis, and EBSCO-host. Articles were selected based on inclusion criteria and evaluated using JBI Critical Appraisal Tools and MMAT. The keywords used were patient discharge OR patient transfer/organization and administration OR discharge plan OR patient transfer OR discharge planning AND Normalization process theory OR normalization process model OR NPT OR NPM. The analysis was carried out using descriptive qualitative and thematic analysis.Results: A total of 8 articles that fulfilled the criteria were included in the analysis. The results suggest that implementing NPT enhances the discharge planning process and facilitates the development of more effective intervention models. NPT was utilized as a framework for data collection, coding, and analysis of the discharge planning implementation process. In addition, NPT is associated with improved coordination among healthcare workers, more effective psychosocial support for families, and increased patient compliance with treatment.Conclusion: The application of NPT inpatient discharge planning allows a deeper understanding of the factors that influence the successful implementation of interventions. The use of NPT in research can help improve the quality of discharge planning by considering aspects of team coordination, patient support, and the effectiveness of evidence-based interventions.Keywords: discharge planning, normalization process theory, patient transition, healthcare coordination